Visually Impaired OLder people's Exercise programme for falls prevenTion (VIOLET): A feasibility study protocol - Skelton, D.; Bailey, C.; Howel, D.; Cattan, M.; Deary, V.; Coe, D.; De Jong, Lex; Gawler, S.; Gray, J.; Lampitt, R.; Wilkinson, J.; Adams, N. (BMJ Group, 2016)
Introduction In the UK, 1 in 5 people aged 75 and over live with sight loss. Visually impaired older people (VIOP) have an above average incidence of falls and 1.3-1.9 times more likely to experience hip fractures, than the general population. Older people with eye diseases are â 1/43 times more likely than those with good vision, to limit activities due to fear of falling. This feasibility study aims to adapt the group-based Falls Management Exercise (FaME) programme to the needs of VIOP and carry out an external pilot trial to inform the design of a future definitive randomised controlled trial. Methods and design A UK based 2-centre mixed methods, randomised, feasibility study will be conducted over 28.months. Stakeholder panels, including VIOP, will make recommendations for adaptations to an existing exercise programme (FaME), to meet the needs of VIOP, promoting uptake and adherence, while retaining required effective components of the exercise programme. 80 VIOP aged 60 and over, living at home, ambulant with or without a walking aid, will be recruited in Newcastle (n=40) and Glasgow (n=40) through National Health Service (NHS) Trusts and third sector partners. Participants randomised into the intervention arm will receive the adapted FaME programme. Participants randomised into the control arm will continue with usual activity. Outcomes are, recruitment rate, adherence and validated measures including fear of falling and quality of life. Postintervention in-depth qualitative interviews will be conducted with a purposive sample of VIOP (N=10). Postural stability instructors will be interviewed, before trial-specific training and following the intervention. Ethics and dissemination Ethics approval was secured through the National Research Ethics Service (NRES) Committee North East, Newcastle and North Tyneside 2. Glasgow Caledonian University was approved as a non-NHS site with local ethics approval. Findings will be disseminated through peer-reviewed journals, national and international conferences. © 2016 Published by the BMJ Publishing Group Limited.